Critical antecedent rainfall conditions for shallow landslides in Chittagong City of Bangladesh - Khan, Younus Ahmed; Lateh, Habibah; Baten, Md Azizul; Kamil, Anton Abdulbasah (Springer International Publishing AG, 2012)
The major landslide events that occurred in Chittagong City in 2007 and 2008 have caused the death of about 140 people and incurred a considerable amount of property loss.At least ten landslide events occurred during the period of 2000–2009, with mainly rainfall as the triggering factor.The critical rainfall condition of the landslide events was analyzed with Gumbel’s extreme value distribution using the historical rainfall–landslide data.The antecedent rainfalls were used for Gumbel’s distribution for the critical rainfall intensity–durations of each historical landslide event.Landslides were correlated with the monthly average as well as the percentile rank of monthly median rainfall. The regression relationship between 30 days of absolute antecedent rainfall intensity (I) and corresponding duration (D) of rainfall responsible for the landslides in the study area was found as I = −15.8ln(D) + 60.49.The calibrated antecedent rainfall analysis showed a relation between I and D as I = −40.5ln(D) + 162.5.The major recent landslide events were related to the extreme rainfall intensities (>40 mm/day) having short period of time (2–7 days).All the major landslide events occurred at much higher rainfall amount compared to the monthly average.However, these rainfall thresholds were statistically based and were not defined hydrological response of rainfall to the soil, as well as other geological conditions associated with slopes.